2008
DOI: 10.1007/s00586-008-0757-z
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral status in adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is a pathological entity of unknown etiology. The causes of osteoporosis or osteopenia in AIS remain undetermined. Whether poor bone quality is an etiologic factor remains controversial. To determine the correlation between low bone mineral status and AIS, a review of literature was performed. After a literature search from 1966 to June 2007 (using Medline, EMBASE, Cochrane DSR, ACP Journal Club, DARE, CCTR, CINAHL and hand searches of references) for studies regarding low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 43 publications
0
71
0
1
Order By: Relevance
“…SNPs association with bone mineral density (BMD) was described [30], the data being, however, incoherent [33]. Low BMD values in IS were indicated in many studies [34] as a possible linkage between ESR1 polymorphism and IS. Estrogen receptor is expressed both in osteoblasts and osteoclasts [35], [36].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs association with bone mineral density (BMD) was described [30], the data being, however, incoherent [33]. Low BMD values in IS were indicated in many studies [34] as a possible linkage between ESR1 polymorphism and IS. Estrogen receptor is expressed both in osteoblasts and osteoclasts [35], [36].…”
Section: Discussionmentioning
confidence: 99%
“…10 , 22-24 In previous studies, patients with AIS were reported to have lower BMI, abnormal leptin bioavailability, and systemic lower bone mass compared with normal controls. 3,5,6,8,25 Together with the current fi nding that the polymorphisms of SNP rs2767485 in LEPR gene were associated with AIS, we can speculate that the abnormal functions of the LEPR gene may contribute to the occurrence of AIS. However, to elucidate the role of SNP rs2767485 in the expression of LEPR gene or the pathway involved for the development of AIS, further functional experiments will be required.…”
Section: Discussionmentioning
confidence: 83%
“…Low BMD status was found in many patients with spine deformity [1517]. Li et al [26] suggest that the prevalence of low BMD in adolescents with AIS is 20% to 38%. A study by Lammert et al [17] showed that the BMD were significantly lower in NF1 patients than normal reference population.…”
Section: Discussionmentioning
confidence: 99%